Peder J. Pedersen & Reinhard Lund (eds.), Unemployment: Theory, Policy, and Structure, Berlin - New York: de Gruyter, 1987, 358 s.; Reinhard Lund, Peder J. Pedersen & Jan Beyer Schmidt-Sørensen (eds.) Studies in Unemployment, Copenhagen: Social Science Mo - A. Buksti, Jacob (Politica, 1988)
Peder J. Pedersen & Reinhard Lund (eds.), Unemployment: Theory, Policy, and Structure, Berlin - New York: de Gruyter, 1987, 358 s.; Reinhard Lund, Peder J. Pedersen & Jan Beyer Schmidt-Sørensen (eds.) Studies in Unemployment, Copenhagen: Social Science Monographs, 1987, 220 s.